INTERACTION OF A LONG PILE OF FINITE STIFFNESS WITH SURROUNDING SOIL AND FOUNDATION CAP - Ter-Martirosyan Zaven Grigor’evich (Vestnik MGSU, 2015)
The article presents the formulation and analytical solution to a quantification of stress strain state of a two-layer soil cylinder enclosing a long pile, interacting with the cap. The solution of the problem is considered for two cases: with and without account for the settlement of the heel and the underlying soil. In the first case, the article is offering equations for determining the stresses of pile’s body and the surrounding soil according to their hardness and the ratio of radiuses of the pile and the surrounding soil cylinder, as well as formulating for determining equivalent deformation modulus of the system “cap-pile-surrounding soil” (the system). Assessing the carrying capacity of the soil under pile’s heel is of great necessity. In the second case, the article is solving a second-order differential equation. We gave the formulas for determining the stresses of the pile at its top and heel, as well as the variation of stresses along the pile’s body. The article is also formulating for determining the settlement of the foundation cap and equivalent deformation modulus of the system. It is shown that, pushing the pile into underlying layer results in the reducing of equivalent modulus of the system.